Досвід використання системи дистанційного навчання Moodle у самопідготовці лікарів-інтернів дитячих анестезіологів - Курочкін, Михайло Юрійович; Kurochkin, M. Yu.; Курочкин, М. Ю. (ВДНЗ України «Українська медична стоматологічна академія», 2015)
Суть використання методики заключается в тому, що на сайті Запорізького державного медичного університету, поряд з іншими факультетами, представлена інформація кафедр факультету післядипломної освіти. Кафедра дитячих хвороб цього факультету має у своєму складі курс дитячої анестезіології, який і пропонує на цьому сайті необхідну інформацію для лікарів-інтернів дитячих анестезіологів. Працюючи в режимі онлайн, лікар-інтерн, майбутній дитячий анестезіолог, має можливість і зобов’язаний, підчас очного періоду навчання на кафедрі, ознайомитись і вивчити певний об’єм лекційного матеріалу, який є на вказаному сайті. Дана система дистанційного теоретичного вивчення лекційного матеріалу Moodle забезпечує належне і достатньо повне ознайомлення майбутніх дитячих анестезіологів з основними розділами дитячої анестезіології і інтенсивної терапії, згідно з програмою навчання. Суть использования методики заключается в том, что на сайте университета, наряду с другими факультетами, представлена информация кафедр факультета последипломного образования. Кафедра детских болезней этого факультета имеет в своем составе курс детской анестезиологии, который и размещает на этом сайте необходимую информацию для врачей-интернов детских анестезиологов. Работая в режиме онлайн, врач-интерн, будующий детский анестезиолог, имеет возможность и обязан, во время очного периода обучения на кафедре, ознакомиться и изучить определенный объем лекционного материала, который есть на указанном сайте. Данная система дистанционного изучения теоретического лекционного материала moodle, обеспечивает должное и достаточно полное ознакомление будущих детских анестезиологов с основными разделами детской анестезиологии интенсивной терапии, в соответствии с программой обучения. According to the education programme, medical interns actively attend lectures, seminars, participate in the work of the scientific, practical and pathological conferences. Increasing the level of theoretical training, they simultaneously learn and improve their practical skills. Department of Children’s Diseases, Faculty of Postgraduate Education of Zaporozhye State Medical University constantly makes efforts in the development and practical implementation of the new, modern teaching methods, both medical interns and practical medical doctors. So, implemented and widely used remote training of doctors- paediatricians different professional orientations. A new and promising method is to grant the lecture material in training system of distance learning Moodle which is effective use of and training of medical interns. Optimization of the studing of lecture material by medical interns of pediatric anesthesiology using distance training system - Moodle. The essence of the technique is that on the site of the University, along with other departments, there are the information of the department of the Faculty of Postgraduate Education. Department of Children’s diseases of this faculty incorporates unit of Pediatric Anesthesiology, which offers the information on this website for medical interns of pediatric anesthesiologists. Working online, medical intern, future pediatric anesthesiologist, has the opportunity and has to get acquainted and learn a certain amount of lecture material that is in the specified website during the period of full-time study at the Department. Lecture material is in the form of «thematic packages», with several lectures in every package. Each lecture is provided with a sufficient number of tables, diagrams, and images on a topic that is taught. It contributes to the clarity of instruction, and improves the absorption of the material. There are 4 or 5 tests on the theme of the material in the end of every lecture, and the time for the answer on which is not restricted. The lecture has been learned, if you receive the 100% correct answers. If the answer of medical intern is “incorrect”, intern must return to the lecture material and to learn it better. The access to the next lecture is possible only after the learning of previous lectures. This system of distance theoretical learning of lecture material provides a proper and sufficiently complete to familiarize future pediatric anesthesiologists with major sections of the Pediatric Anesthesiology and Intensive Therapy, according to the program of the education. After mastering by the medical intern the proposed block of lectures on a particular section of Pediatric Anesthesiology, medical intern must confirm their knowledge and pass the “computer exam” during the limited time. The computer exam includes a set of mixed tests from all lectures in this section of Pediatric Anesthesiology and Intensive Therapy. So, in the end of the unit named «Intensive Therapy of Shocks in Children», which includes four lectures, there are 20 computer tests. For the answering on each question medical intern has only one minute time. For twenty tests you have twenty minutes. The unit of Pediatric Anesthesiology is passed if all lectures of that unit were learned by medical intern, with 100% of correct answers. The training system Moodle is an effective and promising method of distance education of medical interns рediatric anesthesiologists, which requires further implementation and improvement. E-learning system Moodle is a variant of self-study education of the medical intern, in convenient conditions. The training system Moodle allows to check the intern’s participation in this work, personalize their results, helps more objectively assess the level of theoretical training of each medical intern during the period of full-time education at the Department of Children’s Diseases. Videos of multicomponent anesthesia and surgical procedures, accompaning of the lecture material , allows to prepare the medical intern for the future practice.
Опыт использования системы дистанционного обучения moodle в самоподготовке врачей-интернов детских анестезиологов
Keywords: інтернатура; лікарі–інтерни; дитяча анестезіологія; дистанційне навчання; система moodle; internship; medical interns; pediatric anesthesiology; distance education; training system Moodle